2019
DOI: 10.1002/berj.3559
|View full text |Cite
|
Sign up to set email alerts
|

The importance of early phonics improvements for predicting later reading comprehension

Abstract: The role of phonics instruction in early reading development has been the subject of significant conjecture. Recently, England implemented a phonics screening check to assess the phonetic decoding of 6‐year‐old students, to ensure that all students master this foundational literacy skill and attain adequate phonemic awareness in the early years of primary schooling. Students who fail this check are obliged to retake the assessment the following year. In this article, we compare the performance of students who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…The SVR and SVW represent strong interpretational bases for standardized achievement batteries. Intervention research provides support for causal interpretation of these models' components on comprehension and composition (Graham et al, 2012;Double et al, 2019;Conners et al, 2009). Past investigations provide benchmarks for the interrelationships among these constructs within achievement batteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SVR and SVW represent strong interpretational bases for standardized achievement batteries. Intervention research provides support for causal interpretation of these models' components on comprehension and composition (Graham et al, 2012;Double et al, 2019;Conners et al, 2009). Past investigations provide benchmarks for the interrelationships among these constructs within achievement batteries.…”
Section: Discussionmentioning
confidence: 99%
“…Oral language intervention, and strategy instruction, in particular (linked to the language side of these models; Scarborough, 2009), can increase comprehension and composition (Berkeley et al, 2010;Graham et al, 2012;Melby-Lervåg & Lervåg, 2014;Silverman et al, 2020). Decoding or phonics instruction can increase comprehension (Double et al, 2019;Wanzek et al, 2019). Equally important to stress, many components demonstrate skill-by-treatment interactions (Conner et al, 2009).…”
Section: The Simple Views Of Reading and Writingmentioning
confidence: 99%
“…Evidence also suggests that heterogeneous discussion groupings best support comprehension gains, particularly for low-achieving students (Murphy et al, 2017). Also, as with code breaking, teacher-supported opportunities for students' literacy-related play can support reading comprehension and vocabulary development (Cavanaugh et al, 2017;Dickinson & Porche, 2011;Moedt & Holmes, 2020). Finally, because strong relationships with teachers and peers can positively affect reading comprehension (Caleon & Wui, 2019;Jensen, Solheim, & Idsøe, 2019), teachers should incorporate research-based practices that support relationship building, such as collaborative classroom rituals and opportunities for student agency (Boyd, Jarmark, & Edmiston, 2018;Ivey & Johnston, 2015).…”
Section: How To Fostermentioning
confidence: 99%
“…Textual dexterity is a central element to students’ academic success (Double, McGrane, Stiff, & Hopfenbeck, 2019; Pearson et al, 2020; RAND Reading Study Group, 2002). In addition, its various dimensions provide a foundation for human beings to thrive, not only as proficient decoders and comprehenders but also as literate people who can use reading in flexible, meaningful ways to learn things, think critically, and get things done, as well as to connect with and understand others (Greene, 1982; Janks, 2014; Newstreet, Sarker, & Shearer, 2019; Schüller, Birnbaum, & Kröner, 2017).…”
Section: What Kinds Of Readers Should Society Raise?mentioning
confidence: 99%
“…(2017) surveys may speak to the difference in educational policies between England and Australia. Irrespective of the political controversy surrounding the PSC, a large-scale study by Double et al. (2019) has found that students who ‘pass’ the screen achieve better reading comprehension in subsequent years, relative to those who do not ‘pass’.…”
mentioning
confidence: 99%